P59 Utility Of Fib4 Score And Liver Disease In Alpha-1 Antitrypsin Deficiency (a1atd). (10th November 2014) - Bruce-Hickman, D; Saleh, AD; Gooptu, B; Lomas, DA; Thorburn, D; Hurst, JR
Abstract : Introduction: A1ATD is an autosomal co-dominant condition where homozygosity for the Z-allele results, classically, in emphysematous lung involvement, and liver fibrosis dependant on polymerisation rate of aberrant protein. 1 The FIB4 score non-invasively estimates risk of liver fibrosis, 2 but has not previously been investigated in A1ATD. We completed preliminary assessment of the utility of FIB4 in our A1ATD cohort. Whilst the standard of care in A1ATD should be joint respiratory-hepatology services, not all patients are able to access this. A simple tool to guide referral to hepatology services could therefore be clinically useful to the respiratory community. Methods: We report data from 30 PiZZ patients with ultrasound (USS) characterisation of liver disease. An abnormal USS was considered as any abnormality other than cysts, thus including features of cirrhosis and fatty infiltration. FIB4 was calculated as [Age (years)xAST(U/l)]/[Platelets (10 9 )xALT(U/l)]. The most recent lung physiology was recorded as FEV1 (%predicted), diffusion coefficient (KCO, %predicted) and residual volume (RV, %predicted). Body mass index (BMI) was calculated. Results: The 30 patients had a mean age of 54 ± 12.4 years, 14 were male. Lung function showed mean FEV1 1.85 ± 1.12 L (61.3 ± 30.9%), KCO 1.05 ± 0.40 mmol/min/kPa/L (66.4 ± 22.2%) and RV 3.58 ± 1.36 L (171.8 ± 50.4%). The mean FIB4 was 1.76 ± 1.36. Eight (26.7%) patients had liver disease on USS. FIB4 cut-off values of 1.45 and 3.25 were utilised, as they are widely validated. 3 Of patients >3.25, 100% had abnormal scans (PPV 100%), and of patients <1.45, 15.8% had abnormal scans (NPV 82%). FIB4 enabled correct identification of patients with abnormal USS with an area under a ROC curve of 0.642. We demonstrate a relationship between liver involvement in A1ATD and BMI. Those with higher FIB4 had higher BMI (r = 0.453, p = 0.008). We found no relationship between FIB4 and severity of lung involvement. Conclusions: The FIB4 score, calculated from routine laboratory variables and age, may be useful to rule in and out significant liver involvement in A1ATD with reasonable sensitivity and specificity. Further work is required for validation against biopsy, the gold-standard assessment. We confirm a previously noted lack of association between liver disease and emphysema severity, 4 and highlight the association between higher BMI and higher fibrosis risk in A1ATD.